2008
DOI: 10.1002/cne.21911
|View full text |Cite
|
Sign up to set email alerts
|

Tyramine as an independent transmitter and a precursor of octopamine in the locust central nervous system: An immunocytochemical study

Abstract: Octopamine and its precursor tyramine are biogenic amines that are found ubiquitously in insects, playing independent but opposite neuromodulatory roles in a wide spectrum of behaviors, ranging from locomotion and aggression to learning and memory. We used recently available antibodies to octopamine and tyramine to label the distribution of immunoreactive profiles in the brain and ventral nerve cord of the locust. In the brain and all ventral cord ganglia all known octopaminergic neurons were labeled with both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 94 publications
8
82
0
Order By: Relevance
“…TYR and OCT are now well established signaling molecules in invertebrates (Downer et al, 1993;Kutsukake et al, 2000;Anton et al, 2006;Farooqui, 2007;Kononenko et al, 2009). Unlike in vertebrate species, however, they appear to serve the role of bona fide neurotransmitters in invertebrates, functioning as invertebrate versions of vertebrate adrenergic systems (Roeder, 2005;Lange, 2009;Homberg et al, 2013).…”
Section: Invertebrate Trace Aminesmentioning
confidence: 99%
See 1 more Smart Citation
“…TYR and OCT are now well established signaling molecules in invertebrates (Downer et al, 1993;Kutsukake et al, 2000;Anton et al, 2006;Farooqui, 2007;Kononenko et al, 2009). Unlike in vertebrate species, however, they appear to serve the role of bona fide neurotransmitters in invertebrates, functioning as invertebrate versions of vertebrate adrenergic systems (Roeder, 2005;Lange, 2009;Homberg et al, 2013).…”
Section: Invertebrate Trace Aminesmentioning
confidence: 99%
“…As previously described, although less well studied, TYR effects generally appear to functionally oppose those of OCT. As such, TYR-mediated decreases in locomotion (Nagaya et al, 2002;Saraswati et al, 2004), flying behavior (Fussnecker et al, 2006;Vierk et al, 2009), and foraging (Barron et al, 2002;Schulz et al, 2003) have been seen. Roles in sensory perception, particularly taste (Scheiner et al, 2002;Pankiw and Page, 2003) and olfaction (Kutsukake et al, 2000;Anton et al, 2006;Kononenko et al, 2009;Ma et al, 2015), have also been ascribed to TYR. TYRinduced increases in the rate of habituation (Braun and Bicker, 1992) and modification of complex group dynamics (Ma et al, 2015) are reported to occur independently of the conversion of TYR to OCT.…”
Section: E Physiologic Responsesmentioning
confidence: 99%
“…Release and uptake of tyramine in insects may modulate many physiological and behavioral changes related to insect behaviors. 151,175,176 …”
Section: Structural and Function Of Octopaminergic And Tyraminergic Rmentioning
confidence: 99%
“…Octopamine and its precursor tyramine are both derivatives of the amino acid tyrosine, and octopamine and tyramine are believed to function analogously to adrenaline (epinephrine) and noradrenaline (norepinephrine) in vertebrates (Roeder, 2005). Thus, tyramine is now considered to be a neuroactive chemical in its own right, independent of octopamine (Kononenko et al, 2009;Lange, 2009). Octopamine and tyramine regulate diverse physiological and behavioural processes such as courtship, locomotion, learning and memory, and reproduction (Avila et al, 2012;Huang et al, 2016;Roeder, 1999;Selcho et al, 2012).…”
Section: Introductionmentioning
confidence: 99%